Analisis butir soal pengukuran kemampuan berpikir kritis materi pencemaran lingkungan melalui teori tes klasik dan Rasch model - Lathifah Radha Istiyova (Universitas Sebelas Maret, 2025)
ENThis research aims to determine the quality of the items measuring understanding of environmental pollution in one of the Sukoharjo Regency State High Schools for the 2023/2024 academic year. The research method used was descriptive-quantitative with research carried out in February 2024. Data was obtained using a documentary method of 25 multiple-choice questions tested on 36 students. Data analysis uses classical test theory and the Rasch Model. The quality of the questions based on their validity using classical test theory resulted in 25 valid questions, while in the Rasch Model 24 were valid and 1 was invalid. The reliability of the classical test theory is 0.875 (high) and the Rasch Model reliability score is 0.85 (good). Difficulty level in classical test theory, questions are classified into 6 difficult questions, 16 medium and 3 easy. Meanwhile, the Rasch Model questions are distributed into 4 very difficult, 8 difficult, 7 easy, and 5 very easy. The different power aspects using classical test theory obtained 6 questions in the sufficient category and 19 questions in the good category. In contrast, in the Rasch Model three groups of items were obtained based on the item separation index H = 3.34.IDPenelitian ini bertujuan untuk mengetahui kualitas butir soal pengukuran pemahaman konsep pencemaran lingkungan di salah satu SMA Negeri Kabupaten Sukoharjo Tahun Pelajaran 2023/2024. Metode penelitian yang digunakan yaitu deskriptif-kuantitatif dengan pelaksanaan penelitian pada bulan Februari 2024. Data diperoleh dengan metode dokumenter 25 soal pilihan ganda yang diujikan kepada 36 siswa. Analisis data menggunakan teori tes klasik dan Rasch Model. Kualitas soal berdasarkan validitasnya menggunakan teori tes klasik dihasilkan bahwa 25 soal valid, sedangkan pada Rasch Model 24 valid dan 1 tidak valid. Reliabilitas pada teori tes klasik yaitu 0,875 (tinggi) dan skor reliabilitas Rasch Model 0,85 (bagus). Tingkat kesukaran pada teori tes klasik, soal diklasifikasikan menjadi 6 soal sukar, 16 sedang, dan 3 mudah. Sedangkan Rasch Model butir soal terdistribusi menjadi 4 sangat sulit, 8 sulit, 7 mudah, dan 5 sangat mudah. Aspek daya beda menggunakan teori tes klasik diperoleh 6 soal kategori cukup dan 19 soal kategori baik, sedangkan pada Rasch Model diperoleh tiga kelompok butir soal berdasarkan pada indeks separasi butir soal H = 3,34.